Ethanol fermentation using isolated candida tropicalis ATTCCa under non-conventional temperatures - Lim, Ming Gim (Universiti Malaysia Sarawak, (UNIMAS), 2012)
Candida tropicalis isolated from rotten pineapple in Malaysia was used to perfonn ethanol fennentation in hydrolyzed sago starch. The effect of the temperature on the growth of the yeast was studied at 42 and 45°C using batch fennentation mode. From the study, this strain can considered as thenno tolerant yeast due to ability to growth well at 42°C and even to survive at 45°C growing at lower rate. Repeated batch fennentation RBF mode using hydrolyzed sago starch was perfonned to improve the productivity of ethanol at different concentration of 30glL, 40glL, 50 giL, 60glL, 90glL and 100glL for 10 fennentation cycles. In addition, the kinetics of ethanol production, glucose consumption, and by-products of the fennentation was analyzed during the RBF. The rate of glucose consumption of this strain during RBF at 42°C was low. This phenomenon was avoided by lowering the temperature from 42°C to 36°C and consequently high concentration of ethanol was achieved.